Transverse momentum and multiplicity dependence of $$\varLambda _{c}^{+}/D^{0}$$ Λ c + / D 0 ratio in pp collisions at $$\sqrt{s}=13$$ s = 13 TeV - Jun Song; Hai-hong Li; Feng-lan Shao (European Physical Journal C: Particles and Fields, 2023)
Abstract We apply an equal-velocity quark combination model to study the $$\varLambda _{c}^{+}/D^{0}$$ Λ c + / D 0 ratio in the range $$p_{T}\lesssim 10$$ p T ≲ 10  GeV/c in pp collisions at $$\sqrt{s}=13$$ s = 13  TeV. We decompose the ratio into four parts which are related to quark numbers, light-flavor quark $$p_{T}$$ p T spectrum, charm quark $$p_{T}$$ p T spectrum, momentum correlation between light and charm quarks, respectively. Their influence on $$\varLambda _{c}^{+}/D^{0}$$ Λ c + / D 0 ratio is individually studied. The curvature property of light-flavor quark $$p_{T}$$ p T spectrum is the main reason of the non-monotonic $$p_{T}$$ p T dependence of $$\varLambda _{c}^{+}/D^{0}$$ Λ c + / D 0 ratio exhibited in high multiplicity events. Moreover, the multiplicity dependence of $$\varLambda _{c}^{+}/D^{0}$$ Λ c + / D 0 ratio as the function of $$p_{T}$$ p T is mainly because of the multiplicity dependence of light-flavor quark $$p_{T}$$ p T spectrum. Using the light-flavor quark $$p_{T}$$ p T spectrum obtained from experimental data of light-flavor hadrons and charm quark $$p_{T}$$ p T spectrum obtained from FONLL and/or PYTHIA calculations, the $$p_{T}$$ p T dependence of experimental data of $$\varLambda _{c}^{+}/D^{0}$$ Λ c + / D 0 ratio in high multiplicity events and that in low multiplicity events in pp collisions at $$\sqrt{s}=13$$ s = 13 TeV are reasonably understood.